PENGARUH FITUR PEMASARAN MEDIA SOSIAL TERHADAP KEPUTUSAN PEMBELIAN PADA INDUSTRI CEPAT SAJI DENGAN KEPERCAYAAN PADA MEREK SEBAGAI MEDIATOR - Aulia Kusuma Febriyani; Farida Indriani (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT In analyzing the factors of consumer purchasing decisions through social media marketing, companies need to pay attention to the features that exist in social media marketing that influence consumer purchasing decisions. This study aims to analyze the influence of features of interactivity, entertainment, perceived relevance, informativeness, and habit in social media marketing on consumer purchasing decisions in the fast food industry through brand trust as an intervening variable. The required data was collected from visitors to fast food brands McDonalds, KFC and Burger King in Indonesia through a quantitative questionnaire. After getting the desired number of respondents, the data obtained was analyzed with SPSS software. The results show that the features of interactivity, perceived relevance, informativeness, and habits in social media marketing have a direct effect on purchasing decisions, while entertainment features do not have a direct effect on purchasing decisions. The results also show that brand trust is only able to mediate the relationship between informative features and purchase decisions. Theoretically, this paper advances the current literature by exploring the mediating effects of brand trust among the five features of social media marketing and purchasing decisions with new empirical insights from Indonesia, taking into account that previous research like this in the Indonesian region is scarce.